(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2025)
This study explores the application of Systems Analysis Strategies (SAS) to enhance mathematics achievement in post-primary education (PPE) in Cross River State, Nigeria. SAS, a structured approach to problem-solving and decision-making, was employed to address systemic challenges in mathematics education, including instructional inefficiencies, resource constraints, and student engagement. Using a mixed-methods design, primary data were collected through questionnaires, Mathematics Achievement Tests (MAT), and focus group discussions with 600 Junior Secondary School (JSS) students and 60 teachers across six schools in Calabar Municipality. Findings reveal that SAS, particularly through problem-based learning and feedback loops, significantly improved students’ mathematics performance (p < .05) and engagement. Demographic analysis indicated no significant gender-based differences, but urban students outperformed rural peers due to better access to resources. The study highlights the potential of SAS to optimize teaching processes and foster a conducive learning environment. Recommendations include integrating SAS into teacher training and scaling resource allocation to rural schools. This research underscores the transformative potential of systems thinking in addressing educational challenges in developing contexts.